The syndemogenesis of depression: Concepts and examples (Medicine Anthropology Theory, 2018)
Syndemics, or the deleterious interaction of diseases and structural factors, is an essential and increasingly utilized theory with which to address health inequities and how they interact with disease. However, less research has been conducted on syndemogenesis, a process by which a specific disease or structural factor is more likely to exacerbate syndemic interactions. With the increasing incidence and prevalence of depressive symptomology in Westernized nations, and with depression coexisting syndemically with other illnesses, I use depression as a case study to highlight syndemogenic processes in action. Doing so will hopefully aid preventive efforts in these areas.